Fabric-creped absorbent cellulosic sheet having a variable local basis weight - EDWARDS STEVEN L; REEB RONALD R; CHOU HUNG LIANG; YEH KANG CHANG; MCCULLOUGH STEPHEN J; HARPER FRANK D; DWIGGINS JOHN H; SUPER GUY H (2013)
An absorbent cellulosic sheet having a variable local basis weight includes a patterned papermaking-fiber reticulum provided with (a) a plurality of generally machine direction (MD) oriented elongated densified regions of compressed paper-making fibers having a relatively low local basis weight as well as leading and trailing edges, the densified regions being arranged in a repeating pattern of a plurality of generally parallel linear arrays that are longitudinally staggered with respect to each other such that a plurality of intervening linear arrays are disposed between a pair of cross machine (CD) direction aligned densified regions, and (b) a plurality of fiber-enriched, pileated regions having a relatively high local basis weight interspersed between and connected with the densified regions, the pileated regions having crests extending generally in the cross-machine direction of the sheet.